2020
DOI: 10.1098/rspb.2020.1636
|View full text |Cite
|
Sign up to set email alerts
|

Negative mood affects the expression of negative but not positive emotions in mice

Abstract: Whether and to what extent animals experience emotions is crucial for understanding their decisions and behaviour, and underpins a range of scientific fields, including animal behaviour, neuroscience, evolutionary biology and animal welfare science. However, research has predominantly focused on alleviating negative emotions in animals, with the expression of positive emotions left largely unexplored. Therefore, little is known about positive emotions in animals and how their expression is mediated. We used ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
(154 reference statements)
1
11
0
Order By: Relevance
“…Moreover, it would be worth considering how underlying mood states affect changes in facial expressions when confronted with short-term stimuli and thus the interaction between longer-term mood and shorter-term emotional states. This suggestion is in line with the results from a recent study by Clarkson et al ( 45 ), who investigated the interplay between mood and emotions and found that negative mood affected the expression of negative but not positive emotion in mice. It would therefore be valuable to assess changes in response to positive and negative short-term stimuli in addition to the implementation of a mood-inducing treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it would be worth considering how underlying mood states affect changes in facial expressions when confronted with short-term stimuli and thus the interaction between longer-term mood and shorter-term emotional states. This suggestion is in line with the results from a recent study by Clarkson et al ( 45 ), who investigated the interplay between mood and emotions and found that negative mood affected the expression of negative but not positive emotion in mice. It would therefore be valuable to assess changes in response to positive and negative short-term stimuli in addition to the implementation of a mood-inducing treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In view of the importance of positive affective states to positive welfare (Lawrence et al, 2019) this question has important implications for the welfare of free ranging cattle at pasture as well as within the infrastructure of handling facilities and feedlots. Evidence in mice indicates that negative affective states have a cumulative effect that decreases resilience to subsequent aversive events (Clarkson et al, 2020). A tendency toward negative affectivity in flighty cattle would provide an additional limit to their suitability for participation in the animal domestication niche of modern animal production.…”
Section: Discussionmentioning
confidence: 99%
“…The more sustained “disappointment” of traumatized female mice suggested that they were less resilient towards negative emotions. They behaved similarly to mice that experienced affective states like depression and anxiety [ 28 ]. This finding was interesting in view of the fact that post-TBI women show more severe post-concussion symptoms, depression, and anxiety [ 21 ].…”
Section: Discussionmentioning
confidence: 99%